Arbuscular Mycorrhizal Fungi Associated with Bamboo Under Cerrado Brazilian Vegetation - Moura, Jadson Belem de; Souza, Rodrigo Fernandes de; Vieira Junior, Wagner Goncalves [UNESP]; Lima, Isabelly Ribeiro; Mendes Brito, Gustavo Henrique; Marin, Cesar (Springer, 2019)
Most studies on bamboo have evaluated their commercial use but few have investigated their associated arbuscular mycorrhizal fungi (AMF). These symbiont fungi are fundamental on plant growth, nutrient cycling, biodiversity maintenance, etc., particularly on acidic/dystrophic soils as those of the Brazilian Cerrado. This study aimed to characterize the community composition and ecological interactions of AMF associated with the bamboo species Actinocladum verticillatum and Bambusa vulgaris vittata, under Cerrado vegetation in central Brazil. Roots and rhizospheric soil samples of A. verticillatum and B. vulgaris vittata were collected on 12 plots in the Gurupi (Tocantis state) and Porangatu (Goias state) microregions. The roots' mycorrhizal colonization rate, rhizospheric soil' spore density, and the associated AMF genera were evaluated. There were no differences in the radical mycorrhizal colonization rates among the two bamboo species, although B. vulgaris vittata showed higher spore density than A. verticillatum. The genera Acaulospora, Claroideglomus, Diversispora, Scutellospora, Glomus, and Gigaspora were identified in both bamboo species, while Sclerocystis was present only on A. verticillatum. The genera Acaulospora, Diversispora, and Glomus were frequently found together. This study may be a first step to future AMF-based bamboo micro-propagation efforts in the Cerrado Brazilian vegetation.
Keywords: Actinocladum verticillatum; Arbuscular mycorrhizal fungi; Bambusa vulgaris vittata; Cerrado vegetation; Mycorrhizal colonization; Rhizosphere